THE IMPORTANCE OF BEES IN AGRICULTURE - Rahimov M.Yu. (Research Focus International Scientific Journal, 2025)
Nowadays, beekeeping is one of the important sectors developing in our Republic. The importance of bees in agriculture is very great, and about 80% of plants known to mankind form buds and fruits and seeds as a result of cross-pollination. As a result of bees pollinating plant flowers from the outside, they create conditions for improving their species and creating high-yielding varieties, and increase their yield to a certain extent. A number of laws and resolutions have been adopted in our Republic to develop beekeeping, which are of great practical importance in the development of this sector.